2019
DOI: 10.3390/biom9110671
|View full text |Cite
|
Sign up to set email alerts
|

Elicitors and Pre-Fermentative Cold Maceration: Effects on Polyphenol Concentration in Monastrell Grapes and Wines

Abstract: Vitis vinifera L cv Monastrell is the main red grape variety grown for vinification in the Denomination of Origin Jumilla (southeast Spain). Different strategies are still being tested to optimize available resources both in terms of the environment and to achieve wines with better organoleptic and functional characteristics. The objective of this work was to combine two strategies: the application of methyl jasmonate (MeJ), benzothiadiazole (BTH), and methyl jasmonate + benzothiadiazole (MeJ + BTH) elicitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…In the case of acylated anthocyanins, Monastrell is a variety characterized by a low proportion of this group of anthocyanins [ 50 ]; however, 3-acetylglucosides and trans-p -coumaryl derivates of delphinidin, cyanidin, petunidin, peonidin, and malvidin were found; cis - p -coumaroyl and caffeoyl derivatives of malvidin were identified as well ( Table 2 ). The anthocyanin profiles obtained for the different treatments were similar and reflect those found by other authors in the Monastrell variety [ 11 , 30 , 51 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the case of acylated anthocyanins, Monastrell is a variety characterized by a low proportion of this group of anthocyanins [ 50 ]; however, 3-acetylglucosides and trans-p -coumaryl derivates of delphinidin, cyanidin, petunidin, peonidin, and malvidin were found; cis - p -coumaroyl and caffeoyl derivatives of malvidin were identified as well ( Table 2 ). The anthocyanin profiles obtained for the different treatments were similar and reflect those found by other authors in the Monastrell variety [ 11 , 30 , 51 ].…”
Section: Resultssupporting
confidence: 88%
“…If total anthocyanins in grapes ( Figure 1 A,B) and total anthocyanins in the wines ( Figure 2 A,B) are compared, it can be seen that not all the grapes in which a higher concentration of total anthocyanins was observed following the application of elicitors produced wines with a higher concentration of anthocyanins than the control wines, as observed in previous trials [ 16 , 44 , 51 ]. It has been shown that knowledge of the amounts of anthocyanins in grape skins is not sufficient to estimate anthocyanin concentrations in wine, and this lack of correlation has been commonly attributed to the partial retention of these anthocyanins in the skin cells due to the barrier effect of the cell walls [ 60 ].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Elicitors could be described as alternative products produced by plants, microorganisms, or from mineral origin, the result of which is specific to the accumulation of secondary metabolites in plants [1]. The plant resistance activated against pathogens, being one of the mechanisms used to increase the levels of the phenolic composition through the phenylpropanoids route [2,3], is enhanced with the use of elicitors. Accordingly, elicitors can be used to improve the phenolic maturation in grapes, as has been evaluated in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the application of ozonated water to Bobal grapevines not only affected the varietal aroma and polyphenolic content of wines. Elicitors can also be used in grapevines to increase the phenolic content in grapes and wines, so Paladines-Quezada et al [7] combined the application of methyl jasmonate, benzothiadiazole, and methyl jasmonate + benzothiadiazole to Monastrell leaves and this in-field treatment was combined with pre-fermentative cold maceration at the beginning of winemaking. The results showed how the differences between the climatological conditions between the two years studied influenced in the results obtained due to the elicitors applications.…”
mentioning
confidence: 99%